2013
DOI: 10.1214/13-ejs848
|View full text |Cite
|
Sign up to set email alerts
|

A Dual estimator as a tool for solving regression problems

Abstract: This paper discusses a parameter estimation method that employs an unusual estimator called the Dual estimator. For a linear regression model, we obtain two alternative estimators by subtracting or adding a certain vector to the vector of the Ordinary Least Squares Estimator (OLSE). One of them strictly dominates the latter. Moreover, under the normality assumption this estimator is unbiased, and consistent, and has significantly smaller variance than the OLSE. The use of a priori information is a universal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 34 publications
(60 reference statements)
1
6
0
Order By: Relevance
“…As for the James-Stein estimator, the benefit is small as shown above. Furthermore, as shown in [18], efficiency of this estimator decreases with increasing 2 R .…”
Section: The Influence Of the Probabilitymentioning
confidence: 72%
See 4 more Smart Citations
“…As for the James-Stein estimator, the benefit is small as shown above. Furthermore, as shown in [18], efficiency of this estimator decreases with increasing 2 R .…”
Section: The Influence Of the Probabilitymentioning
confidence: 72%
“…[6]) that excluding components corresponding to small eigenvalues may sharply reduce the quality of the estimation and prediction. In particular, in the brief review of opportunities of the shrinkage estimators made in [18] this fact is confirmed by an analysis of the simulation outcomes in [20]. Finally, as to the James-Stein estimator, in our problem, we cannot apply this method in a canonical form [17], as the number of predictor variables is less than three.…”
mentioning
confidence: 66%
See 3 more Smart Citations